2010
DOI: 10.1021/la100942h
|View full text |Cite
|
Sign up to set email alerts
|

Pt3Ti Nanoparticles: Fine Dispersion on SiO2Supports, Enhanced Catalytic CO Oxidation, and Chemical Stability at Elevated Temperatures

Abstract: A platinum-based intermetallic phase with an early d-metal, Pt(3)Ti, has been synthesized in the form of nanoparticles (NPs) dispersed on silica (SiO(2)) supports. The organometallic Pt and Ti precursors, Pt(1,5-cyclooctadiene)Cl(2) and TiCl(4)(tetrahydrofuran)(2), were mixed with SiO(2) and reduced by sodium naphthalide in tetrahydrofuran. Stoichiometric Pt(3)Ti NPs with an average particle size of 2.5 nm were formed on SiO(2) (particle size: 20-200 nm) with an atomically disordered FCC-type structure (Fm3m; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
(80 reference statements)
0
27
0
Order By: Relevance
“…The precursor for Ti, Ti(tetrahydrofuran) 2 Cl 4 , was synthesized from TiCl 4 and distilled THF according to literature procedures. [9][10][11] Precursor solutions were prepared by dissolving 0.04 mmol (14.89 mg) of Pt(1,5-cyclooctadiene)Cl 2 , 0.16 mmol of Ti(tetrahydrofuran) 2 Cl 4 (53.42 mg) and 250 mg of CB (Vulcan XC-72R (E-TEK)) in 20 mL of distilled THF under a dry Ar atmosphere. The precursor solutions were then transferred into a syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precursor for Ti, Ti(tetrahydrofuran) 2 Cl 4 , was synthesized from TiCl 4 and distilled THF according to literature procedures. [9][10][11] Precursor solutions were prepared by dissolving 0.04 mmol (14.89 mg) of Pt(1,5-cyclooctadiene)Cl 2 , 0.16 mmol of Ti(tetrahydrofuran) 2 Cl 4 (53.42 mg) and 250 mg of CB (Vulcan XC-72R (E-TEK)) in 20 mL of distilled THF under a dry Ar atmosphere. The precursor solutions were then transferred into a syringe.…”
Section: Methodsmentioning
confidence: 99%
“…The products were air-stable, black powders. [9][10][11] The Pt-Ti NPs/ CB were annealed in vacuum at different temperatures for 1 hour. Pt NPs/CB was also prepared by a wet-chemical approach using lithium triethylborohydride as a reducing agent.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proved that the intermetallic phase of Pt-Ti has approximately 20% less adsorption energy than that of pure Pt due to the changes in the electronic structure of Pt. [23][24][25] In addition, the component metals of the intermetallic phase, however, in some cases, provide adsorption sites for O 2 , whereas Pt provides adsorption sites for CO (dual site mechanism) in the intermetallic alloys. 26,27 Intermetallic alloys possess both unique surface structures and bulk properties compared to that of usual alloys or component metals that are used extensively for superconductivity, hydrogen storage, and shape-memory related applications.…”
Section: Introductionmentioning
confidence: 99%
“…As the intermetallic ordered structure of Pt alloy nanoparticles has been reported to enhance their durability, mainly because of diminished transition metal dissolution [6][7][8][9][10][11], ordered Pt-Ti alloy nanoparticles have been expected to show higher durability than disordered Pt-Ti alloy nanoparticles. A few groups have reported that carbon-supported ordered Pt-Ti alloy nanoparticles could be prepared via wet chemical approaches, unlike Pt alloys with Y, Sc, or Zr [12,13]. Ti 3+ can be reduced by strong reducing agents such as sodium naphthalenide [14] and potassium triethylborohydride [15].…”
Section: Introductionmentioning
confidence: 99%